MODERN VIEW ON THE ETIOLOGY AND PATHOGENESIS OF THE TEMPOROMANDIBULAR JOINT DYSFUNCTION - S. V. Beinarovich; O. I. Filimonova (Кубанский научный медицинский вестник, 2018)
Aim. The study was conducted to analyze the sources of literature on the etiology and pathogenesis of the temporomandibular joint dysfunction (TMJD) with the reflection of the most urgent and unresolved problems. Materials and methods. A study of Russian and foreign literature of recent years in the databases of RINC, Scopus, Web of Science, Pubmed was conducted.Results. It was revealed that the issue of the etiology and pathogenesis of the TMJD remains open. There are different points of view on the etiology and pathogenesis of this pathology which allow many researchers to not only study the various causes of this pathology known to date but also to work towards finding new etiological factors. The polyetiology of the TMJD explains not only complexity but also requires complex diagnosis and treatment of this pathology.Conclusion. Despite the diversity of views on the etiology and pathogenesis of the TMJ, a number of issues remain that require detailed study. Obviously, it is necessary not only to improve the available methods of diagnosis and treatment but also to develop new methods based on the available various modern views on the problem of the etiology and pathogenesis of the TMJD.